Optical coherence tomography evaluation of the optic nerve head neuro‐retinal rim in glaucoma. (7th September 2018) - Fortune, Brad
Abstract : Clinical examination of the optic disc is a fundamental component of any ophthalmic evaluation, but it is especially important for diagnosis and management of glaucoma. The purpose of this article is to: (1) review the limitations inherent to clinical examination; (2) outline the rationale for adopting into clinical practice quantitative measures of the optic nerve head neuro‐retinal rim tissue integrity derived from current optical coherence tomography imaging approaches; (3) describe recent developments in this area; and (4) highlight a few avenues of active research that hold promise for future translation to clinical practice.